Drastic, Incremental, or Static? An Exploratory Study of Punctuated Equilibrium Theory in Thailand’s Public Expenditure (1960-2022) - Chuayprakong, Pawinee; Metmaolee, Nutchapon (King Prajadhipok’s Institute Journal, 2024)
Previous studies have argued that changes in annual budgets are incremental. Nonetheless, recent research finds that over the long run, annual public budgets feature both stasis and punctuation. Stasis and punctuation represent underreaction and overreaction, respectively, to the social, political, and economic environment, as well as to citizens’ preferences. This pattern of budget changes aligns with the assumptions of Punctuated Equilibrium Theory, which highlights bounded rationality and the garbage can model. To test this theory in the context of Thailand’s public expenditure, this study asked the following questions: “How do Thailand’s annual budgets change over a long period, and which spending categories experience punctuations more frequently than others?” To answer these questions, this study conducted a quantitative analysis using both descriptive and inferential statistics to analyze Thailand’s budget data. The results confirm that Thailand’s public expenditure over an extended period exhibits both stasis and punctuation, consistent with the assumptions of Punctuated Equilibrium Theory for all spending categories, except for the annual budgets of the Ministry of Foreign Affairs, Ministry of Labor, and Ministry of Social Development and Human Security. Additionally, spending categories that experienced more punctuation than others include public enterprises, provincial strategy, and unallocated funds. These categories share common characteristics, such as covering a wide range of policy contexts and not focusing on specific policy areas. Some policy recommendations include encouraging policy advocacy groups to actively take on the roles of watchdogs and policy analysts. As integral parts of democracy and democratic development, these roles can promote more effective information processing, dissemination, and deliberation among all stakeholders. This, in turn, can lead to higher levels of attention and commitment from policymakers and budget actors, ensuring timely and proportionate responses to political, social, and economic circumstances, as well as citizens’ preferences.